A Survey of Payer Perspectives on Cannabis Use Disorder. (10th November 2018) - Kiselica, Andrew M.; Duhig, Amy; Montoya, Ivan; Skolnick, Phil; Floyd, Jennifer; Byars, Cigi
ABSTRACT: Background : Cannabis use disorder (CUD) as described/defined in DSM 5, is characterized by impaired control of marijuana use and related personal, health, and legal consequences. CUD is a serious public health problem, affecting nearly 6 million individuals in the United States. There are no FDA approved medications to treat this disorder. The lack of available treatment options contributes to uncertainties by drug sponsors about formulary and reimbursement decision-making for CUD pharmacotherapies. Objective : To addresses this gap by presenting the first findings on managed care payers' perceptions of CUD treatments and clinical trial end points. Methods : An online survey was conducted with 50 payers from managed care organizations. The survey inquired about perceptions of unmet need in CUD treatment, relevant clinical trial end points, disease knowledge, and likelihood of review of new pharmacotherapies. Results : The majority of payers (62%) reported that they were at least moderately familiar with CUD treatment end points. Most (80%) rated the unmet need for new pharmacotherapies for CUD as at least moderately important. Payers rated the most important end points for clinical trials as abstinence and decreased resource utilization. Most participants said an FDA approved CUD treatment would be formally reviewed by payers within 6 months (58%) or a year (36%). Conclusions : Based on these findings, payers see an unmet need for CUD treatment. Furthermore, FDA-approved pharmacotherapies for CUD will likely be reviewed quickly by payers, especially if data are provided on the likelihood of achieving abstinence and reduced resource utilization.